HOST RESPONSE CHANGES FOLLOWING NON-SURGICAL SUBGINGIVAL INSTRUMENTATION. REVIEW - Liliana Pasarin; Maria-Alexandra Martu; Ionut Luchian; Irina-Georgeta Sufaru; George-Alexandru Maftei; Mihaela Mares; Odette Luca; Sorina-Mihaela Solomon (Romanian Dental Association for Education, 2023)
There is ample literature evidence to support that periodontal therapy has an impact on the local and systemic host immune responses, despite contradicting data from the literature reporting both a decrease and increase in systemic antibody levels following treatment. The clinical guidelines for the treatment of patients with periodontitis stages I-III published from the European Federation of after the patient has been informed about his/her condition, the first step in the treatment process is directed toward motivation, targeting behavioral changes to achieve adequate self-performed oral hygiene practices and controlling local and systemic modifiable risk factors. A systematic review indicates positive associations across patient-reported experiences, self-rated and objectively measured health outcomes in relation to a wide range of areas and settings. Despite patient-reported experiences and patient-reported outcomes of therapy being closely related, there are differences between the two concepts. Frequent re-evaluation of oral hygiene reinforcement outcomes is suggested, aiming to reinforce a patient's motivation and keep the patient up to date with any changes that might occur in the periodontal status, enabling the patient to actively participate in the progress of the treatment plan. In conclusion, short-term perturbations of antibody responses occur during the active phase of periodontal therapy.